Concomitant Dislocation of Proximal and Distal Interphalangeal Joints of Small Finger: A Case Report - Alireza Saied (Journal of Kerman University of Medical Sciences, 2021)
A 24 old man sustained an injury to his right hand when playing soccer as goalkeeper, most probably from a direct strike for the ball or offender foot. On physical examination the injury was limited to the right middle finger, which was swollen, tender an essentially no active motion could be observed in none of the interphalangeal joints. The injury was a close one and no wound or nerve injury was present. No evidence of compartment syndrome was observed. The neurovascular examination was normal. Radiograms were taken immediately which revealed double dislocation of both interphalangeal joints in the right fifth finger. Closed reduction under general anaesthesia was performed and early active and passive range of motion was began as soon as possible. In follow up full range of motion of the joints was retained. The case emphasizes the necessity of whole finger radiologic examination in distal interphalangeal dislocations in the hand.